1997
DOI: 10.1099/00222615-46-5-413
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Ureaplasma urealyticum in urine of patients with systemic lupus erythematosus and healthy individuals by culture and polymerase chain reaction

Abstract: A method was developed to detect Ureaplasma urealyticum in urine by the polymerase chain reaction (PCR). A 457-bp fragment of the urease gene of U. urealyticum was amplified by PCR. Before PCR, components disturbing the amplification had to be reduced. This was possible by diluting the urine 1 in 10 with distilled water and by the extraction of the U. urealyticum DNA. Urine specimens from 41 patients with systemic lupus erythematosus (SLE) and 21 healthy individuals were treated by the dilution method and inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
1
4
2
Order By: Relevance
“…The increased frequency of infection with Mycoplasma hominis and Ureaplasma urealyticum among patients with SLE, reported in the present study, may suggest the participation of environmental factors in the pathogeny of SLE, as has been suggested in the study of Runge et al (1997) 17 , which showed a higher frequency of Ureaplasma urealyticum infection in the urine of women with SLE.…”
Section: Discussionsupporting
confidence: 82%
“…The increased frequency of infection with Mycoplasma hominis and Ureaplasma urealyticum among patients with SLE, reported in the present study, may suggest the participation of environmental factors in the pathogeny of SLE, as has been suggested in the study of Runge et al (1997) 17 , which showed a higher frequency of Ureaplasma urealyticum infection in the urine of women with SLE.…”
Section: Discussionsupporting
confidence: 82%
“…By contrast with the present study, Runge et al . reported a similar frequency of U. urealyticum in urine samples taken from patients with SLE and healthy control individuals with similar sociodemographic characteristics, including age.…”
Section: Discussioncontrasting
confidence: 99%
“…The presence of leukocytosis provided an important clue that lupus was not the cause of the ongoing peritoneal inflammation, as lupus flares are typically associated with low peripheral white blood cell counts. Genital mycoplasmas, including U. urealyticum have been reported to be more prevalent in urine specimens from patients with lupus (4), although subsequent studies have reached conflicting conclusions in this regard (9). The present report demonstrates the ability of U. urealyticum to cause relapsing peritonitis in the setting of CAPD and the value of molecular diagnostic methods in this clinical setting.…”
Section: Case Reportmentioning
confidence: 58%